2020
DOI: 10.1021/acsanm.0c01547
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 Nanoparticle/Fluorinated Reduced Graphene Oxide Nanosheet Composites for Lubrication and Wear Resistance

Abstract: The preparation of TiO2/F-rGO nanocomposites by an in situ synthesis method was discussed, and the nanocomposites were used as lubricant additives. The morphology and structure of TiO2/F-rGO nanocomposites showed that there was an excellent link between TiO2 nanoparticles and F-rGO nanosheets. The tribological results showed that TiO2/F-rGO nanocomposites as lubricant additives displayed a low coefficient of friction and excellent wear resistance capacity. Furthermore, it was illustrated that the TiO2 nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Furthermore, low graphitic loadings (sub-10 wt%) into copper films greatly diminish frictional losses under low contact pressure nano-and macrotribological testing. 44,45,21 Fluorographenes have been utilized in oil-based [46][47][48][49] and polymer-based [50][51][52] lubricating formulations. However, the incorporation of fluorographenes into metal composites have scarcely been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, low graphitic loadings (sub-10 wt%) into copper films greatly diminish frictional losses under low contact pressure nano-and macrotribological testing. 44,45,21 Fluorographenes have been utilized in oil-based [46][47][48][49] and polymer-based [50][51][52] lubricating formulations. However, the incorporation of fluorographenes into metal composites have scarcely been explored.…”
Section: Introductionmentioning
confidence: 99%
“…66 Furthermore, low graphitic loadings (sub-10 wt%) into copper films greatly diminish frictional losses under low contact pressure nano-and macrotribological testing. 38,67,68 Flurographenes have been utilized in oil-based [69][70][71][72][73] and polymer-based [74][75][76] lubricating formulations. However, the incorporation of fluorographenes into metal composites has scarcely been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al discussed the in situ synthesis of TiO 2 /F-RGO nanocomposites and the use of nanocomposites as lubricant additives. TiO 2 nanoparticles and F-RGO nanosheets in nanocomposites have a synergistic lubrication effect and have demonstrated a low friction coefficient and excellent wear resistance . Du et al demonstrated that the excellent lubrication performance of GO-TiO 2 nanocomposites was due to its excellent dispersion stability and the formation of an adsorption film, a carbon protective film, and transfer film, which resulted in good friction reduction and wear resistance .…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 nanoparticles and F-RGO nanosheets in nanocomposites have a synergistic lubrication effect and have demonstrated a low friction coefficient and excellent wear resistance. 15 Du et al demonstrated that the excellent lubrication performance of GO-TiO 2 nanocomposites was due to its excellent dispersion stability and the formation of an adsorption film, a carbon protective film, and transfer film, which resulted in good friction reduction and wear resistance. 16 Nano TiO 2 and graphene can be synergistically combined, resulting in a significant reduction in friction in comparison to pure nano TiO 2 .…”
Section: Introductionmentioning
confidence: 99%